Recent advances of aqueous two-phase flotation system for the recovery of biomolecules - Sankaran, Revathy; Parra Cruz, Ricardo Andres; Show, Pau Loke; Haw, Choon Yian; Lai, Sai Hin; Ng, Eng Poh; Ling, Tau Chuan (Elsevier, 2019)
Recently, aqueous two-phase flotation system (ATPF) has developed as an established technique for separation and purification technology. This process that utilizes the integration principle of aqueous two-phase system and solvent sublation has wide applications in the extraction and purification of biomaterials in biotechnology field. This method has advantages of high recovery yield, high purity, environmentally friendly technique and economical. Additionally, ATPF is easily scalable to large volume which presents an appealing substitute that meets the conditions of industry processes. In the last decade, several researches were conducted to develop this separation process. With the utilization of various integrated method, diverse application of ATPF for numerous product extraction has been explored. This paper discusses the basic principles of ATPF and review on the latest literature works in the advancement of various application and integration of ATPF in the extraction of biomolecules. Comprehensive study on the application of ATPF and the future directions of this new technology in the biotechnology field will be discussed. © 2019 Elsevier B.V.